Obrazowanie ciała rzęskowego za pomocą przezpowiekowej transiluminacji światłem podczerwonym – badanie pilotażowe - Zadorozhnyy, Oleg; Korol, Andrii; Nevska, Alla; Kustryn, Taras; Pasyechnikova, Nataliya (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Background : Near-infrared light is known to pass through human tissues better than visible light. With invisible infrared light, the eye can be illuminated not only through the cornea or the sclera, but also through the eyelid, which can be beneficial in some cases. Purpose : To determine possible use of near-infrared radiation in visualizing ciliary body structures by transpalpebral transillumination. Material and methods : The study cohort included 15 people (30 eyes) with no visible lesions of the anterior segment of the eye; 20 patients (20 eyes) with absolute glaucoma before the laser transscleral cyclodestruction; and 15 patients (15 eyes) with intraocular tumours of the ciliary body. In all cases, a color photo of the anterior eye segment, infrared transillumination and ultrasound scan were performed. Results : In healthy individuals and in patients with absolute glaucoma prior to laser cyclodestruction, a ciliary body and its structures were imaged. In patients with intraocular tumours, near-infrared transillumination made it possible to visualize the tumour and to estimate its localization relative to the ciliary body structures. Conclusion : Transpalpebral near-infrared transillumination accurately estimates the projection of ciliary body structures to the sclera. Near-infrared transillumination can be used for ciliary body visualisation in patients with absolute glaucoma prior to laser cyclodestruction. Near-infrared transillumination helps visualize intraocular tumours and determine their projection to the sclera, which can be used for diagnostic purposes and during destruction of the tumour.